The role of digital orientation, digital capability and digital innovation on the relationship of environmental dynamism towards FMCG SME’s performance - Anggit Primadita Karina; Rifelly Dewi Astuti (Proceeding of the International Conference on Family Business and Entrepreneurship, 2022)
Innovation activities have become the basis for a new digital infrastructure among businesses. Business actors in this study referring to SMEs need to develop digital orientation and digital capabilities in building digital innovation, where increasing these three factors can lead to a competitive advantage to improve company performance for SMEs, especially in the FMCG industry. The main objective of this research is to examine the role of dynamics of business environment on competitive advantage and performance through digital orientation, digital capability, and digital innovation. This study uses a quantitative approach collected from 216 FMCG SMEs in Indonesia. We intend to find the relationship between each variable and the conclusion of these studies using SEM analysis. The results of the SEM analysis show that there is a significant positive relationship between dynamic environment to digital orientation and digital capability. In addition, digital orientation and digital capability have a significant direct positive relationship to digital innovation. Moreover, digital innovation has a significant positive impact to performance directly, and also mediated by competitive advantage. However, digital orientation and digital capability do not have a direct significant effect on competitive advantage.